2020
DOI: 10.1021/acssuschemeng.0c03559
|View full text |Cite
|
Sign up to set email alerts
|

ZSM-5-Supported Graphene-Encapsulated Nickel Nanoparticles: Formation, Properties, and Exceptional Performance in Lipid Hydrogenation

Abstract: Graphene-encapsulated nickel nanoparticles (Ni@C) were loaded on Zeolite Socony Mobil (ZSM)-5 for lipid hydrogenation to produce biojet fuel. Ni@C and ZSM-5 exhibit an efficient and synergistic catalytic activity, and the strong chemical interaction between graphene and nickel significantly improves the hydrogenation capacity of the catalyst. The graphene layers strengthened the dispersion of nickel, reduced the size of Ni@C to ∼3.6 nm, and kept the valence state of nickel at 0. According to the hydrogenation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…25,26 In addition, supported non-noble metal catalysts and metal oxides have also been focused due to their low cost and high catalytic activity. 27,28 For example, Ni/HBeta catalyst was tested in the catalytic hydro-processing of microalgae oil, resulting in a yield of 99% diesel. 29 Li et al 30 reported that the NiO−LiZSM-5 catalyst exhibited higher catalytic activity than that of Ni-LiZSM-5 in the HDO of oleic acid.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 In addition, supported non-noble metal catalysts and metal oxides have also been focused due to their low cost and high catalytic activity. 27,28 For example, Ni/HBeta catalyst was tested in the catalytic hydro-processing of microalgae oil, resulting in a yield of 99% diesel. 29 Li et al 30 reported that the NiO−LiZSM-5 catalyst exhibited higher catalytic activity than that of Ni-LiZSM-5 in the HDO of oleic acid.…”
Section: Introductionmentioning
confidence: 99%